ITS Academy: una grande opportunità per i giovani e per il paese - Ghirardi, Marco (Chimica nella Scuola, 2022)
ITSs were founded about ten years ago. However, this important educational opportunity is little known. Most people believe that ITS stays for Industrial Technical Institutes, i.e., High School Institutes. This misunderstanding also affects the national press. The collaboration between school and the productive system is a goal of the ITSs; this is necessary to enhance orientation and to reduce unemployment. In this paper we describe the structure of ITSs, their regulatory evolution and their institutional objectives. To give a concrete example, we make specific reference to the ITS TAM in Biella.